Millennials Response on The Existence of The First Sharia Electronic Money in Indonesia - Halimah, Imtyazul Hikmah; riza, Alex fahrur (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2022)
The growth of technology this day makes it a necessity in daily human life such as electronic money. There are so many issuers that have been registered at Bank Indonesia. An issuer even tries to add Sharia features to its electronic money. Although the sharia label has become common in Indonesian society, there is still scepticism about sharia labels on some products. This study aims to determine the switching intention of millennials to use sharia electronic money in Indonesia using the UTAUT2 as a research model. The population in this study is all users of LinkAja electronic money. The sampling technique used purposive sampling; the number of samples was 168 users. Data analysis techniques used are Structural Equation Model and Partial Least Square (SEM-PLS), the data processing applications using Smart-PLS 3.0. The results of this study indicate that the two independent variables, social influence and facilitating conditions, do not affect the intention to switch. However, five other independent variables, performance expectancy, effort expectancy, hedonic motivation, price value, and habit, positively and significantly affect the intention to switch to using Sharia electronic money.